2014
DOI: 10.1096/fj.13-248450
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the β‐barrel domain of BamA from Escherichia coli

Abstract: In gram-negative bacteria, the assembly of outer membrane proteins (OMPs) requires a β-barrel assembly machinery (BAM) complex, of which BamA is an essential and evolutionarily conserved component. To elucidate the mechanism of BamA-mediated OMP biogenesis, we determined the crystal structure of the C-terminal transmembrane domain of BamA from Escherichia coli (EcBamA) at 2.6 Å resolution. The structure reveals 2 distinct features. First, a portion of the extracellular side of the β barrel is composed of 5 mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
137
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(148 citation statements)
references
References 48 publications
11
137
0
Order By: Relevance
“…Rather, the glycine likely plays a structural role and is required to produce a stable, folded β-barrel. In fact, crystal structures of the BamA β-barrel indicate that G771 is adjacent to residues F738 and D740, which interact with the highly conserved residue R661 in loop 6 (8,9). These interactions between loop 6 and residues on the inside of the barrel may be important in stabilizing the barrel structure, and we hypothesize that larger amino acids at position 771 may disrupt these interactions.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Rather, the glycine likely plays a structural role and is required to produce a stable, folded β-barrel. In fact, crystal structures of the BamA β-barrel indicate that G771 is adjacent to residues F738 and D740, which interact with the highly conserved residue R661 in loop 6 (8,9). These interactions between loop 6 and residues on the inside of the barrel may be important in stabilizing the barrel structure, and we hypothesize that larger amino acids at position 771 may disrupt these interactions.…”
Section: Resultsmentioning
confidence: 88%
“…However, the mechanism by which β-barrel assembly proceeds is only beginning to be elucidated. Structures of the components of the bacterial β-barrel assembly machine (BamA-E) have been determined recently, and several hypotheses about how they facilitate the assembly of its substrates have been proposed (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The β-barrel component BamA contains a kinked β-strand, which might allow substrate proteins to be inserted by passing laterally from the lumen of the BamA β-barrel into the hydrophobic membrane (18).…”
mentioning
confidence: 99%
“…Although structures have been reported for the orthologs of the Omp85 family, including FhaC, TamA, and BamA, in Gram-negative bacteria (35,36,(43)(44)(45)(46), no structure has been reported for either Sam50 in mitochondria or Toc75 or OEP80 in chloroplasts. Here we report the structure of Toc75, from A. thaliana, consisting of the N-terminal linker and three tandem POTRA domains (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent X-ray crystallography and cryo-EM studies reported the structures of several Omp85 family members, including FhaC, TamA, and BamA (28,(36)(37)(38)(43)(44)(45)(46)(47). Given the conservation of key features, these structures serve as models for Toc75, albeit with low sequence identity (7%, 7%, and 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…We uncover the critical role of an extracellular b-sheet for FhaC secretion activity. Interestingly, corresponding surface regions of the E. coli Omp85 transporter BamA were also found to be essential for function 33,34 .…”
Section: Discussionmentioning
confidence: 99%